Determining the effects of tryptophan:lysine ratios in diets containing 30% dried distillers grains with solubles on growth performance of 157- to 285-lb pigs - Nitikanchana, S.; Usry, J.L.; Boyd, R.D.; Zier-Rush, C.E.; McGrath, M.; Tokach, Michael D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 2,298 pigs (half gilts and half barrows, PIC TR4 × 1050; initially 157 lb) were used in a 52-d study to determine the effects of increasing tryptophan:lysine ratios in diets containing 30% dried distillers grains with solubles (DDGS) on the growth performance of finishing pigs raised in a commercial environment. Pens of pigs were balanced by initial weight and randomly allotted to 1 of 6 dietary treatments in a completely randomized design within gender; each pen contained 23 pigs and each treatment had 16 to 17 replications. Treatments were arranged as a 2 × 6 factorial with main effects of gender (gilts or barrows) and standardized ileal digestible (SID) tryptophan:lysine ratio (2 positive control diets with no DDGS containing SID tryptophan:lysine ratios of 17 or 21% of lysine and 4 diets containing 30% DDGS with SID tryptophan:lysine ratios of 15, 17, 19, or 21% lysine). Overall (d 0 to 52), no gender × treatment interactions were measured. Pigs fed 30% DDGS had poorer ADG, ADFI, and F/G (P < 0.01, P = 0.04, and P = 0.01, respectively) compared with those fed the corn-soybean meal diet. In pigs fed diets without DDGS, those fed the 17% SID tryptophan:lysine ratio tended to have better F/G (P = 0.09) compared with pigs fed the 20% SID tryptophan:lysine ratio. Increasing SID tryptophan:lysine ratio from 15 to 21% in diets containing 30% DDGS had no effect on ADG, ADFI, or F/G. For carcass characteristics, feeding 30% DDGS reduced HCW, loin depth, and lean percentage (P < 0.01, P < 0.01, and P = 0.04, respectively). For carcass traits, in pigs fed diets without DDGS, those fed the 21% SID tryptophan:lysine ratio had decreased backfat (P = 0.04) and greater lean percentage (P = 0.04) compared with pigs fed 17% SID tryptophan:lysine ratio. Increasing the SID tryptophan:lysine ratio from 15 to 21% in the 30% DDGS diets increased (linear, P < 0.01) percentage carcass yield and had a tendency (linear, P = 0.07) to increase HCW. These results suggest an opportunity to improve carcass traits and carcass value by increasing the SID tryptophan:lysine ratio for late finishing pigs that are fed high levels of DDGS.
Keywords: Swine; amino acid ratio; DDGS; Lysine; Tryptophan; Finishing pig